PENANAMAN KARAKTER MANDIRI PADA PESERTA PELATIHAN MENJAHIT DI BALAI LATIHAN KERJA CILACAP (Unnes Civic Education Journal, 2022)
Sewing training is a trainings that trainees able to set up a sewing business at home. The sewing training at BLK Cilacap carried out efforts to instill independent character for the trainees. The results showed that the process of internalization independent characters was carry out by sewing training instructors and instructors from outside institutions. The character planting process consists of three stages, namely: 1) At the planning stage the instructor selects prospective sewing training participants through interview selection, and prepares a soft skills curriculum. 2) At the implementation stage using character-planting methods such as teaching, exemplary, habituation, motivation and rule enforcement. While the material for character internalization from the soft skill curriculum, including motivational material by Cilacap Job Training Center and its partners, improving ethical standards in the work environment, forming responsibility, work productivity, building a positive self-concept at work, developing critical thinking skills in solving problems and seeking solutions, build integrity as a professional workforce and develop teamwork capabilities. At the implementation stage, there are also activities, namely sewing training, on the job training and softskills training. 3) The independent character evaluation stage is based on the instructor's observation, through the question and answer method, and a direct warning from the training instructor. Supporting factors for cultivating independent characters at Cilacap Job Training Centre are the desire in sewing training participants to become entrepreneurs, complete facilities. While the inhibiting factors for the cultivation of independent characters are the lack of teaching staff, capital difficulties and incomplete sewing tools when the graduates of the sewing training participants set up a sewing business at home.